Cartografia das doenças transmissíveis em Maringá-PR : 2010-2016 - Oliveira, Antonio de (2018)
The understanding of the relations that come directly and indirectly between the environment and the human being can help in the studies of the transmissible diseases that affect the population of a certain place. It is known that the disease is a manifestation of the individual and the health situation is a manifestation of the place, but it must not be forgotten that diseases can occur due to the interference of the human being on the environment. In order to understand how, because and in what way this situation occurs, geography aims to clarify human beings' relations with the environment, but the meaning of each disease and its dynamics will require new lessons to explain the impact of the first relationships with the occurrence of the second. Therefore, in the study of the dynamics of the disease, notes on the disease are required, such as incubation, transmission and other factors related to the environment and the individual. In order to facilitate the understanding of this process, the spatial analysis of the data is essential, in order to obtain the standard and even temporal comparison. Thus mapping is the most effective way to record and understand such relations whose locations are geographic. Therefore, the purpose of this study was to study the dynamics of Leprosy, Tuberculosis, Meningitis, Varicella and ACL, transmissible diseases of compulsory notification in the urban area of Maringá from 2010 to 2016, based on proposals of cartographic synthesis with the use Graphic Semiology and Graphic Modeling. And as a general result it can be affirmed that the diseases studied are influenced to a great extent by the social vulnerability linked to the urban infrastructure, fact that remains constant in different parts of the city, and that thus characterize the dynamics of the diseases is to comprehend them in the global, conceiving the biological and environmental together with the economic and social